Runx1 mediates the development of the granular convoluted tubules in the submandibular glands. - Hitomi Ono Minagi; Safiye Esra Sarper; Hiroshi Kurosaka; Koh-Ichi Kuremoto; Ichiro Taniuchi; Takayoshi Sakai; Takashi Yamashiro (PLoS ONE)
The mouse granular convoluted tubules (GCTs), which are only located in the submandibular gland (SMG) are known to develop and maintain their structure in an androgen-dependent manner. We previously demonstrated that the GCTs are involuted by the epithelial deletion of core binding factor β (CBFβ), a transcription factor that physically interacts with any of the Runt-related transcription factor (RUNX) proteins (RUNX1, 2 and 3). This result clearly demonstrates that the Runx /Cbfb signaling pathway is indispensable in the development of the GCTs. However, it is not clear which of the RUNX proteins plays useful role in the development of the GCTs by activating the Runx /Cbfb signaling pathway. Past studies have revealed that the Runx /Cbfb signaling pathway plays important roles in various aspects of development and homeostatic events. Moreover, the Runx genes have different temporospatial requirements depending on the biological situation. In the present study, the GCTs of the SMG showed a remarkable phenotype of, which phenocopied the epithelial deletion of Cbfb, in epithelial-specific Runx1 conditional knock-out (cKO) mice. The results indicate that Runx1 works as a partner of Cbfb during the development of the GCTs. We also discovered that the depletion of Runx1 resulted in the reduced secretion of saliva in male mice. Consistent with this finding, one of the water channels, Aquaporin-5 (AQP5) was mislocalized in the cytoplasm of the Runx1 mutants, suggesting a novel role of Runx1 in the membrane trafficking of AQP5. In summary, the present findings demonstrated that RUNX1 is essential for the development of the GCTs. Furthermore, RUNX1 could also be involved in the membrane trafficking of the AQP5 protein of the acinar cells in the SMG in order to allow for the proper secretion of saliva.